An Empirical Assessment of Diversity in Fish Species: Case Study of Madhubani District, India - Maimoon, Razdan; Kole, Soma (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Sarisab Pahi Chaur is a wetland sites in the Madhubani district, Bihar has rich fish diversity. The present investigation was undertaken the status of fish diversity and seasonal impacts on them in Sarisab Pahi Chaur of Madhubani, Bihar. A total number of 29 species representing 17 families of 9 orders of class Actinopterygii were identified from Sarisab Pahi Chaur wetland, the various species of order Cypriniformes 49% and Clupeiformes 16% dominated in the wetland followed by order Siluriformes 15%, Perciformes 12%, Channiformes 6%, Symbrachiformes, Beloniformes, Anguilliformes and Mugiliformes respectively. In present investigation species diversity of fishes of Sarisab Pahi Chaur, ranged between the lowest 0.943 June, 2021 and the highest 1.346 May, 2022. Species evenness (J) of fishes of Sarisab Pahi Chaur, varied from the lowest 0.787 July, 2021 and the highest 0.933 March, 2022 during the investigation period. Species richness (d) of fishes of Sarisab Pahi Chaur, varied from the lowest 6.603 June, 2021 and the highest 12.411 May, 2022. The value of Shannon-Wiener diversity, Species richness and the Evenness in different months are the different value which is depends upon the fish density and physico-chemical parameters of water of wetland. The paper takes into account to explore the importance of wild variety in fish seed production and its support in sustainable livelihood development.